Arrays of graphene-quantum dots-supported DNA oligonucleotides as self-indicating porphyrin carriers - Monteiro, Ana R. (2023)
The functionalization of deoxyribonucleic acid (DNA) with nanomaterials is a promising strategy to optimize the loading and efficiency of drugs in targeted clinical therapies. Herein we report a novel approach to construct arrays comprising blue- (B) or aqua green- (AG) emitting ethylenediamine-modified graphene quantum dots (GQDs) and DNA oligonucleotides that are able to fold into different structures, namely G-quadruplexes (G4s). The obtained results indicate that GQDs partially modulate the conformation of oligonucleotides, resulting in GQDs-DNA bioconjugates with higher affinity to carry 5,10,15,20-tetrakis(1-methylpyridinium-4-yl)porphyrin (TMPyP), in comparison to non-modified DNA sequences. TMPyP shows a higher affinity, expressed by a lower dissociation constant (KD), to GQDs-B-G4-1 (0.229 μM) and to GQDs-AG-G4-1 (KD of 0.326 μM) in comparison with non-modified G4-1 (KD of 0.440 μM). The carrier systems with the highest affinity to TMPyP correspond to GQDs-AG with telomeric unimolecular G4 sequence (GQDs-AG-G4-2, KD of 0.111 μM) and GQDs-AG with a non-G4 sequence (GQDs-AG-non-G4, KD of 0.110 μM), followed by their analogues with GQDs-B. While uncovering terra incognita, it is anticipated that GQDs-DNA arrays may be potential photoluminescent nanovehicles to carry other cationic anticancer drugs and allow more targeted therapies.